A Comparative Study of Motivating Potential Score of Employees of Public and Private Commercial Banks: An Assessment of Demographics Influence (Global Journal of Management and Business Research, 2014)
The article presents a theoretical-empirical reflection about concepts, models, and practices of Job Diagnostic Survey Model for computing Motivating Potential Score (MPS) of employees of public and private commercial banks in Bangladesh with demographics influence. Empirical part of this study comprises 130 samples, have been collected through a structured questionnaire. The study reveals that demographic factors such as education, marital status, gender, experience, age, salary and designation have insignificant influence on Motivating Potential Score. The study also reveals that Motivating Potential Score of private commercial bank is slightly higher than public commercial bank but mean difference is statistically insignificant on one way ANOVA statistics at the five percent level of significance. The study concludes that MPS properties closer to a particular job irrespective to the demographics and nature of the organization.
Keywords: MPS; skill variety; task identity; task significance; autonomy feedback from job; commercial bank